Secularization and Attribution: How Mainline Protestant Clergy and Congregants Explain Church Growth and Decline. (24th October 2017) - Flatt, Kevin N; Haskell, D Millard; Burgoyne, Stephanie
Abstract: This article analyzes explanations for growth and decline given by 22 clergy and 128 congregants from 21 mainline Protestant churches in Canada, including both growing and declining congregations. Both clergy and congregants attributed growth and decline to a wide range of external and internal causes, but people in declining churches were more likely to attribute them to external factors outside churches' control, while people in growing churches tended to attribute them to the characteristics of the churches themselves. Both groups overwhelmingly relied on human explanations rather than supernatural ones, with some exceptions from growing church participants. We argue that these results align with the predictions of attribution theory and also reflect a high degree of internal secularization that is more advanced in the declining churches. We discuss the role of theological factors in these differences and suggest possible implications for understanding church growth and decline.